Urban Spaces Efficiency Qualification in Vertical Residential Buildings: Al -Amal Residential Complex as Case Study - Alghezi, Badr; Al-Saidi, Adil (Al-Nahrain Journal for Engineering Sciences, 2025)
Planning standards in most countries especially in Iraq have become old and inadequate and do not fulfill the growing needs of people in the meanwhile. Also, it does not provide solutions for the society problems since it does not came from deep and modern study of the society needs and problems. In Iraq, there is a clear neglect of the urban spaces in residential buildings. As the challenges of 21st century, climate change, pollution and health crises requires infrastructure which is capable of keeping up with people needs and capable of providing healthy life, wellbeing and economic recovery.  The study explores the efficiency of urban spaces in one of the Iraqi new residential complexes which is Alamal residential complex to determine the factors that affect urban spaces in vertical residential buildings in Iraq. The evaluation of the spaces was done by using direct observation method and questionnaire method. Results revealed that the spaces in such residential complex were active and efficient but it needs more spaces to be available since vertical residential buildings have high density of people. Also, there was a good care of urban spaces that fulfill the needs of children to play and also spaces which are friendly to old people. Most participants in the questionnaire have declared that the public urban space (space 3) was the most used, most favored space since it has many activities and facilities which support social activities between people living in the residential complex.